Lifetime adverse pregnancy outcomes and associated factors among antenatal care booked women in Central Gondar zone and Gondar city administration, Northwest Ethiopia - Muluneh, Atalay Goshu; Asratie, Melaku Hunie; Gebremariam, Tesfamichael; Adu, Aynalem; Enyew, Mihretu Molla; Cherkos, Endeshaw Admasu; Melkamu, Senetsehuf; Berta, Martha; Mamo, Worku; Kassahun, Dawit; Tsega, Nuhamin Tesfa; Kebede, Azmeraw Ambachew; et al. (Frontiers in Public Health, 2022)
Background In developing countries, adverse pregnancy outcomes are major public health issues. It is one of the leading causes of neonatal morbidity and mortality worldwide. Despite the fact that ending prenatal mortality and morbidity is one of the third Sustainable Development Goals (SDG), the burden of the problem continues to be a huge concern in developing countries, including Ethiopia. Hence, this study aimed to determine the prevalence and associated factors of lifetime adverse pregnancy outcomes among antenatal care (ANC) booked women in Northwest Ethiopia. Methods An institutional-based cross-sectional study design was conducted in Northwest Ethiopia, between March 2021 and June 2021. A multi-stage stratified random sampling technique was employed to recruit participants. An interviewer-administered and checklist questionnaire were used to collect the data. The data were entered into Epi-data version 4.6 software and exported to Stata version 16 for analysis. The binary logistic regression model was fitted to identify an association between associated factors and the outcome variable. Variables with a p-value of < 0.05 in the multivariable logistic regression model were declared as statistically significant. Results In this study, the lifetime prevalence of adverse pregnancy outcome among study participants was 14.53% (95%CI: 11.61, 18.04). Road access to the health facilities (AOR = 2.62; 95% CI: 1.14, 6.02) and husband-supported pregnancy (AOR = 2.63; 95 CI: 1.46, 4.72) were significantly associated with adverse pregnancy outcomes. Conclusions More than one in 10 reproductive age women had adverse pregnancy outcome throughout their life. Road access to health facilities and husband-supported pregnancy were statistically significant factors for adverse events in pregnancy. Therefore, it is better to give more attention to expanding infrastructure like road accessibility and increasing husband-supported pregnancy to reduce adverse pregnancy outcomes.